The effect of input mode, input enhancement and number of exposures on the learning and processing of binomials in the L2 - Alotaibi, Sara (2020)
An important feature of language is that it permits the understanding and production of an infinite set of word combinations (Chomsky, 1965). However, an important percentage of our productions involve prefabricated units or chunks. Native English speakers will say “fish and chips” over “chips and fish”, even though the two phrases carry the same meaning. Phrases like “fish and chips” are referred to as binomials, which are phrases formed by two content words from the same lexical class joined by a coordinating conjunction, generally with a conventional word order. Of the vast array of formulaic subtypes, binomials remain relatively unexplored in terms of learning and processing. In this thesis, I conducted three studies to gain greater insight into the development of binomial knowledge and the factors that influence learning, including input modes, number of exposures, and input enhancement. My main aim was to discover the most effective learning conditions for L2 learners to develop declarative and procedural knowledge of binomials. In the first study, I used offline measures (paper and pencil tests) to examine the effects of three different input modes (reading-only, listening-only, and reading-while-listening) and number of exposures on the acquisition of declarative knowledge of binomials. In the second study, I utilised eye-tracking with two main objectives. The first was to investigate whether learners develop procedural knowledge of binomials from exposure to varied modes of input, and whether the number of exposures to target items would play a role. The second objective was to examine whether the addition of auditory input (the reading-while-listening condition) would affect the processing of binomials. This is a particularly important question because identifying how reading vocabulary differs in reading-only and reading-while-listening might explain the conflicting findings in the literature on the advantages associated with the reading-while-listening mode. In the third study, my aim was to examine whether employing strategies that make the lexical items more salient for learners in the input, such as written input enhancement, might further support the development of procedural knowledge. I also employed eye-tracking and presented the same materials as in Study 2, with the only difference being that some of the target items were now highlighted in red colour. The results of Study 1 revealed that L2 learners were capable of developing declarative knowledge of the ‘correct’ order of binomials and the associations between their components from various modes of input. The reading-while-listening mode was more effective than the listening-only mode, and as effective as the reading-only mode. In Study 2, findings showed that seeing novel binomials repeatedly led to fewer fixations and shorter reading times. Learners also took less time to process existing binomials than novel ones; however, with increased exposures, novel binomials began to be processed like existing ones, demonstrating the important role of exposure in the development of procedural knowledge. Further, the comparison of reading patterns between reading-only and reading-while-listening showed that it made no difference for L2 learners whether they exclusively read or simultaneously read and listened to the texts. For L1 readers, the presence of auditory input resulted in slower processing. Study 3 demonstrated that when the words comprising a binomial were enhanced (in red colour), both L1 and L2 learners allocated greater attention to processing them in comparison to unenhanced items. Importantly, shorter reading times for enhanced novel binomials were observed after only four exposures, while this affect appeared later in the case of unenhanced novel binomials, after six exposures. This indicates that learners needed fewer number of encounters to gain procedural knowledge of binomials when target items were enhanced. In sum, the findings from these studies have shown that successful learning and faster processing of formulaic language across different input modes is associated with the number of exposures to novel binomials. However, the results indicate a complex relationship between number of exposures and other variables (e.g. input mode, aspects of vocabulary knowledge and input enhancement), which collectively influence L2 vocabulary acquisition.